PUSAT PERTUMBUHAN EKONOMI DI WILAYAH PESISIR BARAT SELATAN ACEH - Fakhruddin Fakhruddin; Cut Risya Varlitya; Ema Alemina; Sufirmansyah Sufirmansyah; Irham Iskandar (MediaTrend, 2022)
This research aims to identify alternative areas as the new growth pole and formulate a development strategy in the South West region of Aceh. The methods used are Klassen typology, gravity models, and breaking point. The scope of this research covers 7 (seven) districts and 1 (one) city for the period of 2011 to 2016. The entire district and city are assumed to be an economic unit treated as a parent area for all districts/cities. The results showed that, firstly, there could be 2 (two) growth poles if we divided by coastal areas, namely Nagan Raya District for the west coastal region of Aceh and  Southwest Aceh District for the southern coastal region of Aceh.  However, Nagan Raya Regency is the alternative choice for the new growth pole in South West  region of Aceh. Secondly, the improvement of the agricultural, forestry and fishery sectors as well as the development of human resources in accordance with the needs of the labor market is necessary to be able to develop the new center of economic growth.